2013
DOI: 10.1002/app.38981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porous emulsion‐templated monoliths from a pulp mill by‐product

Abstract: Black liquor is a by-product of the paper mill Kraft process that deserves more valorization than its present use as low-grade fuel. In this work, we present an original approach allowing the preparation of macroporous interconnected monolithic materials using as-received black liquor as main raw material. The process involves the formulation of an oil-in-water medium internal phase emulsion as soft templating porosity medium. The oil (internal phase) used is castor oil, whereas the continuous phase is constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…The characterization of black liquor was reported in our previous paper . Thermogravimetric analysis of the dry matter revealed that it contained around 40 wt % of inorganics.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…The characterization of black liquor was reported in our previous paper . Thermogravimetric analysis of the dry matter revealed that it contained around 40 wt % of inorganics.…”
Section: Methodsmentioning
confidence: 78%
“…We have previously reported the preparation of foams from emulsion‐templated Kraft black liquor by crosslinking with epichlorohydrin (Figure ). However, others approaches may be followed to obtain porous monolithic materials from an aqueous solution of precursor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocks of porous polymeric lignin hybrids can be obtained using black liquor directly, using the high internal phase emulsion (HIPE) technique [103]. Again, epichlorhydrin is used as cross-linker in the presence of a surfactant.…”
Section: Microporous and Nanoporous Materialsmentioning
confidence: 99%
“…For that, a series of macroporous monolithic columns with different average pore size from 300 up to 2000 nm was prepared and applied for enzyme immobilization. Despite a lot of existing experimental data on the synthesis of different monolithic materials , the possibility of predictable tuning of monolith pore size was not properly explored.…”
Section: Introductionmentioning
confidence: 99%